A phase II trial of BAY 43‐9006 (sorafenib) (NSC‐724772) in patients with relapsing and resistant multiple myeloma: SWOG S0434. (10th June 2014) - Srkalovic, Gordan; Hussein, Mohamad A.; Hoering, Antje; Zonder, Jeffrey A.; Popplewell, Leslie L.; Trivedi, Harsha; Mazzoni, Sandy; Sexton, Rachel; Orlowski, Robert Z.; Barlogie, Bart
Abstract The authors assessed the overall response rate, including confirmed complete response (CR) and partial response, in patients with relapsed/refractory multiple myeloma treated with sorafenib. Qualitative and quantitative toxicities associated with this regimen were evaluated. Patients were eligible if they had a confirmed diagnosis of refractory or relapsed (RR) multiple myeloma (MM) with measurable monoclonal protein. Patients had to have adequate renal, hepatic, hematologic, and cardiac function with a Zubrod performance status of 0–2. Patients were given 400 mg sorafenib by mouth twice daily for 28‐day treatment cycles. These patients were followed up for a maximum of 3 years to assess responses and adverse events. Twenty‐three patients were enrolled. Of these, five were found to be ineligible for the following reasons: four had insufficient documentation of the baseline disease and one patient did not have measurable disease. All eighteen eligible patients were evaluable for toxicities. Three patients experienced grade 4 toxicities: one with thrombocytopenia, one with anemia, and one with renal failure. Four of the eighteen eligible patients were not assessable for response due to removal from protocol treatment prior to adequate disease assessment. Specifically, three were removed for either grade 4 toxicity or progression of disease and one was removed per patient choice (due to reasons unrelated to treatment). Of the 18 patients who were assessed for toxicities, 5 (27.8%) received at least one fully dosed cycle, 2 (11.1%) of whom had all cycles fully dosed. No responses were observed on this study of the 14 patients who were assessable for response. All patients have discontinued protocol treatment as of August 2008. Overall survival at 12 months was 50% (95% CI 27–73%) and median progression‐free survival was 1.2 months (95% CI 1.0–5.4). The trial did not exhibit activity by the International Uniform Response Criteria for MM. Further research should focus on combination therapy of sorafenib with standard treatments in selected patients with RR MM.